Upaya Pencegahan Penyakit Tidak Menular Melalui PemeriksaanDan Konseling Kesehatan Di Manado Town Square - Lea Shintya; Ailine Yoan Sanger (Servitium Smart Journal, 2026)
on-communicable diseases (NCDs) are a major public health problem causing high morbidity and mortality rates worldwide. According to the World Health Organization, NCDs kill 41 million people every year, accounting for 71% of all global deaths. In Indonesia, NCDs contribute to 73% of deaths with 26% occurring in adulthood. This study aims to increase community awareness about the importance of NCD prevention through health screening and counseling. The method used was a community service activity in the form of health screening involving 65 participants (37% male, 63% female) from Manado Town Square visitors aged ≥19 years. Examinations included blood pressure, random blood glucose, total cholesterol, uric acid, and anthropometry, followed by health counseling based on examination results. The results showed that 65% of participants had suboptimal blood pressure, 8% had abnormal blood glucose (pre-diabetes and diabetes), 42% had borderline high or high cholesterol, and 22% had high uric acid. These findings indicate high prevalence of NCD risk factors in the community, necessitating continued efforts in health education, early detection, and health promotion to prevent increased NCD cases in North Sulawesi.